The repression of mètis within digital organizations. (1st September 2020) - Holford, W. David
Abstract : Numerous organizations are placing great emphasis on such techniques as evidence-based protocols to automation and artificial intelligence (AI) with the aim of improving efficiency and maximizing profitability. Such instrumental techniques attempt to formalize all manner of environmental phenomena through abstraction and categorization. They have also reduced organizational capability to deal with dynamic environmental complexities, uncertainties and ambiguities. The aim of this paper is to examine organizational approaches relying heavily on formalized/automated protocols in aviation, medicine and other professional domains targeted by AI development. Such approaches repress the human capability known as mètis, which organizations require to deal successfully with dynamic ambiguities in the form of unexpected emergencies. Mètis is briefly explained, and examples of organizational barriers preventing its manifestation are given.